2022
DOI: 10.1172/jci.insight.156319
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte proinflammatory phenotypic control by ephrin type A receptor 4 mediates neural tissue damage

Abstract: Circulating monocytes have emerged as key regulators of the neuroinflammatory milieu in a number of neuropathological disorders. Ephrin type-A receptor 4 (Epha4) receptor tyrosine kinase, a prominent axon guidance molecule, has recently been implicated in the regulation of neuroinflammation. Using a mouse model of brain injury and GFP bone marrow (BM) chimeric approach, we find neuroprotection and lack of significant motor deficits that is marked by reduced monocyte/macrophage cortical infiltration, and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Controlled Cortical Impact (CCI). Mice were injured as previously described [39][40][41][42][43]. Briefly, ketamine 100mg/kg, xylazine 10mg/kg, and Buprenorphine SR (0.5 mg/kg) were administered subcutaneously for anesthetic and analgesia before surgery.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled Cortical Impact (CCI). Mice were injured as previously described [39][40][41][42][43]. Briefly, ketamine 100mg/kg, xylazine 10mg/kg, and Buprenorphine SR (0.5 mg/kg) were administered subcutaneously for anesthetic and analgesia before surgery.…”
Section: Animalsmentioning
confidence: 99%
“…Images were acquired using a Nikon ECLIPSE Ti2 Inverted confocal microscope with a motorized stage and a Nikon C2 laser system. Five coronal sections were analyzed by a blinded investigator using the Optical Fractionator probe from MBF StereoInvestigator software (MicroBrightField, Williston, VT, USA) and an upright Olympus BX51TRF motorized microscope (Olympus America, Center Valley, PA, USA) as previously described [39,40,42,43]. Contours for the DG and hilus were created, and the optical fractionator's grid size was set at 150x150mm with a 75x75mm counting frame.…”
Section: Animalsmentioning
confidence: 99%
“…It is well established that these monocyte subsets infiltrate the brain following traumatic injury in mice and that the CCR2-CCL2 axis is essential for the recruitment of the Ly6C hi subset [ 51 ]. Classical monocytes are involved in phagocytosis and pro-inflammatory responses; intermediate cells exclusively express CCR5 and mediate antigen presentation, while non-classical cells are involved in complement and Fc gamma-mediated phagocytosis and adhesion [ 52 , 53 , 54 ]. A subset of non-classical monocytes express CD9 and SLAN, which suggests increased efferocytosis and migration functions compared to the SLAN-negative population [ 53 , 55 ].…”
Section: Distinct Role For Microglia and Other Myeloid Cells In The N...mentioning
confidence: 99%
“…Monocyte depletion studies demonstrated that peripheral-derived monocytes contribute to the pathophysiology of several neurological disorders, including but not limited to Alzheimer’s disease (AD), intracerebral hemorrhage, traumatic brain injury, and multiple sclerosis [ 51 , 52 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. Mice receiving intravenous injections of clodronate had reduced numbers of CCR2+Ly6c hi monocytes infiltrating the brain following injury, suggesting subset control modulates tissue damage [ 52 ]. Importantly, the use of CCR2-/- mice revealed that altering monocyte influx directly affects the production of type1 interferon genes in resident microglial subsets [ 47 ].…”
Section: Distinct Role For Microglia and Other Myeloid Cells In The N...mentioning
confidence: 99%
See 1 more Smart Citation